A Summary of Current Understanding Regarding Children with Autism Spectrum Disorder Who Are Deaf or Hard of Hearing - Szarkowski, Amy; Mood, Deborah; Shield, Aaron; Wiley, Susan; Yoshinaga-Itano, Christine (Seminars in Speech and Language, 2014)
This article provides a consensus perspective based on the authors' expertise and the limited available literature regarding our understanding of children with an autism spectrum disorder (ASD) who are deaf or hard of hearing (D/HH). The challenges in the accurate identification of an ASD in children who are D/HH, including red flags for a potential ASD and screening and assessment for ASD, are described in this article. Additionally, strategies to guide professionals in their communication about a possible ASD with families and to frame the need for expanding aspects of communication important for this group of children are suggested.
Keywords: Deaf; hard of hearing; autism spectrum disorder; assessment